Analisis Social Return On Investment (SROI) dalam Penerapan Program Ketahanan Ekonomi dan Pangan Rumah Tangga Desa Dendang - Dayang Septasawitri; Bulan Prabawani; Hari Susanta Nugraha (Jurnal Administrasi Bisnis, 2023)
Business activities in the current era are not only profit-oriented but highlight the value of sustainability. Due to global problems such as poverty and limited availability of resources, a sustainable company means that the company can maintain and improve the environmental life around the company. One of the company's efforts to create business sustainability is through a corporate sustainability strategy or the implementation of corporate social responsibility (CSR) and a form of business ethics and social investment. To determine the effectiveness of a program, carried out an evaluation. This study aims to analyze the CSR program of PT SMM by using the Social Return On Investment (SROI) method. This study uses a qualitative descriptive approach to describe the implementation of PT SMM's CSR program and analyze the success of the program through the results of the SROI value. The results of the SROI calculation in this program show a ratio of 7.84, meaning that every investment made by PT SMM is Rp. 1,- getting a benefit of Rp. 7.8,-. This program can be categorized as successful because it can exceed the ratio of 1 in the SROI. If viewed from the economic, social, and environmental aspects, this program has good sustainability potential and deserves to be continued.